1998
DOI: 10.1111/j.1442-200x.1998.tb01994.x
|View full text |Cite
|
Sign up to set email alerts
|

CD48 expression on leukocytes in infectious diseases: Flow cytometric analysis of surface antigen

Abstract: Background: The function of CD48, one of the pan leukocyte cell surface antigens, is not yet well understood. CD48 was recently shown to enhance the CD40-mediated activating signal to B lymphocytcs. As CD-IX is one of the activation antigens of monocytes. neutrophils and lymphocytes, a change of its expression on the cells could be expected in infectious diseases. Methods and results: Leukocytes from 27 healthy controls and 97 patients with various infectious diseaseswere stained with antiLCD48 antibody and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…CD48 has been reported to be elevated in the serum and on the surface of hemopoietic cells from patients with leukemia and infectious diseases (12,14). Assessment of both peripheral blood and nasal polyp eosinophils from atopic asthmatics demonstrated that CD48 was indeed elevated in patients with allergic disease compared with nonatopic controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CD48 has been reported to be elevated in the serum and on the surface of hemopoietic cells from patients with leukemia and infectious diseases (12,14). Assessment of both peripheral blood and nasal polyp eosinophils from atopic asthmatics demonstrated that CD48 was indeed elevated in patients with allergic disease compared with nonatopic controls.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, CD48 expression is increased in several infectious diseases, including varicella, measles, rubella, mononucleosis, streptococcus tonsillitis, sepsis, and appendicitis (14).…”
mentioning
confidence: 99%
“…In fact, the only hematopoietic cell populations in mice that distinctly lack CD48 expression in mice are neutrophils and a subset of long-term hematopoietic stem cells (LT-HSCs) [59, 60]. However, in humans CD48 is also found on neutrophils and other HSC types [61, 62]. …”
Section: Cd48 Structure and Expressionmentioning
confidence: 99%
“…Exposure to cytokines such as IFNα, IFNβ and IFNγ can increase CD48 expression on human peripheral blood mononuclear cells [63]. Monocytes and lymphocytes have elevated CD48 expression in patients with viral and bacterial infections [61]. Patients with EBV infection or arthritis exhibit elevated levels of soluble CD48 in the serum [52].…”
Section: Cd48 Structure and Expressionmentioning
confidence: 99%
“…Clinically, membrane and soluble CD48 expression increases under inflammatory conditions and has been shown to be elevated in patients with systemic inflammatory disorders, hematopoietic malignancies, infections, and allergic diseases [ 3 , 8 , 9 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%